Open Defecation Free in Improving Clean and Healthy Lifestyle Behavior in Parakan Hamlet Kertaharja Village Cimerak Sub-District - Dierayani, Allysa Putri; Pratiwi, Denisa Lestari; Nurjaman, Diman; Madani, Fathi Makia; Sajidah, Febi Zulfa; Amelisqi, Lusi Bilqis; Saparudin, Miftahul Rizki; Pratama, Muhamad Risky; Fitriyani, Seni D; Nita, Sri; Nurohmah Dona, Tiara Gita; Shofiatun Nisa, Wafa; Nur Elfaz, Zam Zam; Risma, Neng; Nuraeni, Neni; Saputra, Jumadil; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Ownership and use of healthy latrines is one of the indicators of the Clean and Healthy Behavior (PHBS) program in the household environment. Based on the results of the PHBS study, nationally the percentage of households using healthy latrines (39%), in urban areas (60%) is much higher than in rural areas (23%). The percentage of households using healthy latrines in West Java Province is slightly above the national average of 39.6%. The use of latrines is an important health problem both in rural areas and in Kertaharja Village. In the development of healthy latrines in Parakan Hamlet, two points were built, namely in the Karang loa block RT 08 Rw 03 and the Gatah block RT 12 RW 05. However, even though the latrines have been built, their utilization is still not optimal. where people still carry out open defecation activities such as in open land. Therefore, KKN UMTAS students carry out counseling activities on clean and healthy living behavior in every household along with Open Defecation Free (ODF) activities, where counseling is given to the people of Kertaharja Village, especially in the Parakan Hamlet area. The purpose of this activity is to improve clean and healthy living behavior (PHBS) in Kertaharja Village, especially in Parakan Hamlet by building healthy latrines after socialization, site surveys, triggering and pre-development, then developing a declaration from the local community about the use of latrines that have been built. . The declaration of Open Defecation Free (ODF) was held on September 7, 2022, which was attended by the community, village officials, students and was attended by the Deputy Regent of Pangandaran and the Camat of Cimerak